Józef Starkman (1847–1892) – the promoter of medical knowledge regarding home treatment of sick children - Bednarz-Grzybek, Renata; Krasińska, Izabela (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
This article aims to present the views of Dr. Józef Starkman regarding the home treatment of sick children and young persons. The main point of the article underlinesthe importance of maintaining good hygiene in the rooms where sick people, including the children and the young spent their time. Starkman highlighted the roles of physical activity, mental hygiene, physical development, proper clothing and balanced, healthy eating. In his opinion, childhood habits tended to impact on adulthood. According to Starkman, the reasons for numerous health problems and disorders should have been defined on the basis of imbalanced diet, neglecting hygiene and poor sanitary conditions. He also emphasised deficiencies in physical activity and spiritual development as regards the children’s and youth’s time spent both at home and at school.
Keywords: health; hygiene; Józef Starkman; upbringing